2009
DOI: 10.1185/03007990903212682
|View full text |Cite
|
Sign up to set email alerts
|

Gastroduodenal toxicity of low-dose acetylsalicylic acid: a comparison with non-steroidal anti-inflammatory drugs

Abstract: Data suggest that ASA causes significant gastroduodenal damage even at the low doses used for cardiovascular protection. These effects (both systemic and possibly local) may be pharmacodynamically distinct from the gastroduodenal toxicity seen with NSAIDs. Studies are required to establish strategies for improving the tolerability of low-dose ASA, allowing patients to continue to benefit from the cardiovascular protection associated with such therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 111 publications
0
20
0
1
Order By: Relevance
“…Gastrointestinal (GI) erosions and bleeding are two of the most common toxic side-effects associated with the administration of NSAIDs. These effects have been observed even with small prophylactic doses of aspirin (81 mg/d) 10 . Approximately 50% of patients taking NSAIDs on a long-term basis may develop mucosal damage in the small intestine 11 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gastrointestinal (GI) erosions and bleeding are two of the most common toxic side-effects associated with the administration of NSAIDs. These effects have been observed even with small prophylactic doses of aspirin (81 mg/d) 10 . Approximately 50% of patients taking NSAIDs on a long-term basis may develop mucosal damage in the small intestine 11 .…”
Section: Introductionmentioning
confidence: 98%
“…Finally, we evaporated the solvent under vacuum, and we purified the corresponding amines by flash chromatography. All products (10)(11)(12) were used immediately after purification to obtain the corresponding ammonium salts (13-15) described below.…”
Section: Ch)mentioning
confidence: 99%
“…Aspirin also raises the risk of hemorrhagic stroke and other major bleeding (Baigent et al, 2009), significant gastro duodenal damage even in the low doses used for cardiovascular protection (Yeomans et al, 2009). Avoid use in severe liver disease (Lacy et al, 2011), because liver toxicity is reported by aspirin (Bjorkman, 1998) days or weeks are required to develop hepatotoxicity (Zimmerman, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…As úlceras gástricas são caracterizadas por danos na mucosa e estão predominantemente relacionadas à infecção por Helicobacter pylori, utilização de ácido acetilsalicílico (Yeomans et al, 2009), fármacos anti-inflamatórios não esteroidais (AINES), tabagismo e ao consumo de álcool (Soberg et al, 2010). Estas lesões resultam basicamente de um desequilíbrio entre mecanismos de defesa (secreção de muco, regeneração celular e agentes protetores endógenos) e fatores agressivos (secreção de ácido e pepsina) (Maity et al, 2003).…”
Section: Introductionunclassified